2019
DOI: 10.1177/1558944719864451
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Distal Scaphoid Resection for Scapho-Trapezium-Trapezoid Arthritis

Abstract: Background: The purpose of this study was to describe the technique of arthroscopic resection of the scaphoid head and evaluate both the clinical and radiographic results of scapho-trapezium-trapezoid osteoarthritis cases. Methods: Seventeen cases (13 men and 4 women) with a mean age of 57 years (24-74 years) were operated on from 2002 to 2015. Inclusion criteria were nontraumatic radial-sided wrist pain without improvement after 4 months of conservative treatment and positive radiographic images demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Iida et al 23 studied the impact of arthroscopic resection of the distal pole of the scaphoid and found good results, as long as the resection did not exceed 3 mm and there was no associated carpal instability (DISI). Luchetti et al 24 found similar results, adding that the technique does not contraindicate cases of associated trapeziometacarpal arthrosis, as long as it is treated concomitantly. Mathoulin and Darin 25 had already published their series using this same technique, with the exception that, in the long term, an impingement phenomenon could occur at the joint level, justifying the addition of pyrocarbon implants to maintain physiological carpal height.…”
Section: Scaphotrapezoidal Joint (Stt)mentioning
confidence: 76%
See 1 more Smart Citation
“…Iida et al 23 studied the impact of arthroscopic resection of the distal pole of the scaphoid and found good results, as long as the resection did not exceed 3 mm and there was no associated carpal instability (DISI). Luchetti et al 24 found similar results, adding that the technique does not contraindicate cases of associated trapeziometacarpal arthrosis, as long as it is treated concomitantly. Mathoulin and Darin 25 had already published their series using this same technique, with the exception that, in the long term, an impingement phenomenon could occur at the joint level, justifying the addition of pyrocarbon implants to maintain physiological carpal height.…”
Section: Scaphotrapezoidal Joint (Stt)mentioning
confidence: 76%
“…Iida et al 23 estudaram o impacto da ressecção artroscópica do polo distal do escafoide e encontrou bons resultados, desde que a ressecção não excedesse os 3mm e que não houvesse instabilidade carpal associada (DISI). Luchetti et al 24 encontraram resultados semelhantes, acrescentando que não contraindica a técnica para casos de artrose trapeziometacarpal associada, desde que tratada concomitantemente. Mathoulin e Darin 25 já haviam publicado sua série com essa mesma técnica, com a ressalva que, a longo prazo, poderia ocorrer um fenômeno de impingement a nível da articulação, justificando o acréscimo de implantes de pirocarbono para manter a altura carpal fisiológica.…”
Section: Articulação Escafotrapeziotrapezoidal (Stt)unclassified
“…It requires less immobilization time and has fewer complications than arthrodesis, but can create midcarpal instability and DISI deformity, or even worsen such problems if already existent. 30,[45][46][47] Most authors nowadays recommend the association of some type of carpal stabilization to the distal scaphoid resection. 10,[42][43][44] Some authors propose the use of metal interposition arthroplasties for such a purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Bei einer isolierten STT-Arthrose hebt eine arthroskopische Resektionsarthroplastik den Knochenkontakt zwischen Os trapezium, Os trapezoideum und Os scaphoideum auf. Arthroskopische Resektionen erfordern arthroskopische Erfahrung ([ 36 ]; Abb. 6 ).…”
Section: Therapie Der Handgelenkarthroseunclassified